The impact of foreign direct investment on green technology progress in China on two-carbon background: taking trade openness into consideration - Yi, Ming; Xu, Longyu; Zhang, Tian; Ao, Lian; Sun, Meng (Frontiers in Environmental Science, 2025)
With the proposal of the carbon peaking and carbon neutrality strategy, the concept of green and low-carbon began to take root, and the influence of foreign direct investment on the progress of green technology is attracting more and more attention. Based on the panel data of 30 provinces in China from 2011 to 2020, this study examines the effect of green technology progress on FDI and its geographic and policy heterogeneity by using generalized least square regression method, and discusses its mechanism combined with the moderating effect of trade opening. The results show that: (1) the introduction of FDI has a significant positive effect on green technology progress, while the moderating effect of trade openness weakens the positive effect, which has a negative impact on green technology progress; (2) The results of the heterogeneity analysis suggest that the Belt and Road Initiative is an important factor in the moderating effect of trade openness. Beneficiary provinces along the Belt and Road are able to reap the positive effects of trade in terms of green technological advances, while regional differences based on geographic location gradually weaken. This study provides a new policy reference for boosting green technology progress in China and different provinces and helping to achieve the two-carbon goal from the two aspects of introducing FDI and coordinating trade openness.